Turnover Intention Pada PT Maisya Makmur Ditinjau Dari Lingkungan Kerja Sosial Dan Disiplin Kerja Dengan Kepuasan Kerja Sebagai Variabel Intervening - Syafika Kamila; MM Tri Susetyaning Mildawani (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to analyze turnover intention at PT Maisya Makmur in terms of the social work environment and work discipline with job satisfaction as an intervening variable. This research method was carried out by distributing questionnaires to employees of PT Maisya Makmur with 80 research respondents who were obtained using saturation techniques. This research data was processed using the SmartPLS software method version 3.2.9. The research results show that the social work environment contributes significantly to turnover intention, work discipline contributes significantly to turnover intention, and job satisfaction contributes significantly to turnover intention. The social work environment contributes significantly to job satisfaction, work discipline contributes significantly to job satisfaction. The social work environment through job satisfaction as an intervening variable contributes significantly to turnover intention. Work discipline through job satisfaction as an intervening variable contributes significantly to turnover intention.